Pelatihan Alat Peraga Penggaris Geser Untuk Meningkatkan Pemahaman Berhitung Siswa SD - Rospala Hanisah Yukti Sari (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Teaching aids are media that can help stimulate students' skills, thoughts, attention and desires so that they can stimulate student learning activities. On the other hand, using teaching aids can create space for students to be able to participate in every learning process. In fact, at SDN 2 Kereng Bangkirai class III and SDIT Hasanka class II, learning activities have not used teaching aids. The props that are made and used are counting boards made from cardboard. This teaching aid is used in the learning process for class III students at SDN 2 Kereng Bangkirai and class II at SDIT Hasanka. The aim of learning using these teaching aids is to facilitate students in the learning process and the hope is that by using these props, learning activities can be more active and enjoyable in learning activities, and will not make students bored in learning so that their material skills will be better.